MAKNA MOTIF LUKISAN MEGALITIK TUTARI [The Meaning of Tutari Megalitical Motif] - Djami, Erlin Novita Idje; Suroto, Hari (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2017)
In the megalithic period, humans living around the Tutari hill have poured their minds through paintings on rocky boulders spread across the slopes of Tutari Hill. Painting Megalithic Tutari describes ideas or ideas and behavior of society in the form of symbols, which express the natural environment and socio-cultural conditions of the community. The existence of these paintings is very interesting to know the shape and meaning. The purpose of this paper is to know the meaning of motifs megalithic painting Tutari. The methods used are stylistic analysis and contextual analysis. The motifs of the paintings contained in the Tutari Megalithic Site are human motifs, anthropomorphic images, flora, fauna, cultural objects, and geometric. These motifs have meaning related to the beliefs, daily life, and environmental circumstances of Lake Sentani in prehistoric times.  ABSTRAKPada masa megalitik, manusia yang hidup di sekitar bukit Tutari telah menuangkan alam pikiran mereka melalui lukisan pada bongkah-bongkah batu yang tersebar luas di lereng Bukit Tutari. Lukisan Megalitik Tutari menggambarkan gagasan atau ide dan perilaku masyarakat dalam bentuk simbol-simbol, yang mengekspresikan lingkungan alam dan keadaan sosial budaya masyarakatnya. Keberadaan lukisan-lukisan tersebut sangat menarik untuk diketahui bentuk dan maknanya. Tujuan tulisan ini adalah untuk mengetahui makna motif lukisan megalitik Tutari. Metode yang digunakan adalah analisis stilistik dan analisis kontekstual. Motif lukisan yang terdapat di Situs Megalitik Tutari berupa motif manusia, gambar antropomorfik, flora, fauna, benda budaya, dan geometris. Motif-motif ini memiliki makna yang berkaitan dengan kepercayaan, kehidupan seharihari, serta keadaan lingkungan Danau Sentani pada jaman prasejarah.